2020
DOI: 10.1002/cbin.11442
|View full text |Cite
|
Sign up to set email alerts
|

MAPRE1 promotes cell cycle progression of hepatocellular carcinoma cells by interacting with CDK2

Abstract: Targeting cyclin-dependent kinases (CDKs) is a promising method of therapy for cancer. Unfortunately, the efficacy of CDK inhibitors in hepatocellular carcinoma (HCC) is limited, due in part to incomplete understanding of cell cycle progression and a lack of specific biomarkers to adequately identify which patients may be responsive to CDK inhibitors. In the present study, we report that microtubuleassociated protein RP/EB family member 1 (MAPRE1), a gene involved in cell cycle and microtubule regulation, is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Based on the latest research, silencing circPVT1 enhances the radiosensitivity in NSCLC via regulating microRNA(miRNA)-1208 [ 13 ]. Another study revealed that circRNA_100565 facilitates cisplatin-resistant NSCLC via adjusting miR-337-3p/a disintegrin and metalloproteinases 28 (ADAM28) axis in proliferation, apoptosis and autophagy [ 14 ]. CircSOX13 is a type of circRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the latest research, silencing circPVT1 enhances the radiosensitivity in NSCLC via regulating microRNA(miRNA)-1208 [ 13 ]. Another study revealed that circRNA_100565 facilitates cisplatin-resistant NSCLC via adjusting miR-337-3p/a disintegrin and metalloproteinases 28 (ADAM28) axis in proliferation, apoptosis and autophagy [ 14 ]. CircSOX13 is a type of circRNA.…”
Section: Introductionmentioning
confidence: 99%
“…But molecular mechanism of HCC is still less studied. An important role in HCC is cell cycle regulator [ 19 – 21 ]. Our study also demonstrates that the functional enrichment of DEGs is significantly upregulated in the cell cycle pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no investigation about PPAR signaling pathway in HCC, which is reserved for further research. Cell cycle pathway was a critical mechanism, by which many genes could promote HCC cell proliferation [50][51][52]. The reasonable explanation was that lnc-CCNY-1 promote tumor progression of HCC by downregulating PPAR signaling pathway and upregulating cell cycle.…”
Section: Discussionmentioning
confidence: 99%